Sistem Pendukung Keputusan Seleksi Anggota Paskibraka Kabupaten Pamekasan - Moh Fahmi Maulidanitamyizi; Hoiriyah Hoiriyah; Hozairi Hozairi (J-INTECH ( Journal of Information and Technology), 2023)
This study evaluates the use of the Decision Support System (SPK) with the AHP method for the selection of Paskibraka members in Pamekasan Regency. The criteria used in this study were Body Posture (PT), Height (TB), and Health (K). The results of ranking the first priority criteria are Height (K = 0.70), second is Height (TB = 0.21), and third is Body Posture (PT = 0.08). From the results of the alternative ranking of the selected paskibraka participant candidates, A8=0.22, A7=0.20, A6=0.16, A5=0.12, A4=0.09, A3=0.06, A2=0.06, and A3=0.05. The contribution of the SPK application will help the committee evaluate the recruitment process of team members objectively.